Futurum w koncepcji Słowackiego - Kasperski, Edward (Śląskie Studia Polonistyczne, 2012)
The author of the article discusses the structure, aspects, usage and role of the time category of futurum in Juliusz Słowacki’s works against the background of a Romantic philosophy of time and artistic solutions in this field. He refers this futurum particularly to the Romantic cult of the past, absorbtion of the present, reflection on eternity and time defragmentation into separated and mutually isolated moments (the very phenomenon is known in the literature of the subject as Momentanisierung der Zeit). He explains the presence and up-to-dateness of futurum in Słowacki by means of four main factors: a) anticipation of reception, b) heterotelic orientation of writing wishing to change the reality, and, thus interest in its shape in the future, c) autobiographic (existential) situation of the poet confronted with a prospect of forthcoming death, d) historiosophic vision exposing a necessary extermination of existing forms, and a must to form new ones. Słowacki shared August Cieszkowski’s opinion, who considered the future as “an integral part of the history presenting a fulfillment of human fate”, but radicalized him because he replaced a cumulative vision of “the end of history” as a synthesis of everything that humanity achieved in the course of its development with a substitute vision, namely a vision of a “progress on the piles of the corps”. The end of the history equaled the extermination of old forms and constitutes their new and better opening.